2023
DOI: 10.1109/tasc.2023.3244510
|View full text |Cite
|
Sign up to set email alerts
|

Improved Crystalline Quality and Self-Field $J_{\mathrm{c}}$ in Sequentially Vacuum-Multilayered YBCO Thin Films on Buffered Metallic Templates

Abstract: The effect of simple in situ vacuum treatment between the sequentially multilayered YBCO thin films by pulsed laser deposition is investigated. The vacuum treatment during the growth intervals is observed to have a diminishing effect on the formation of structural defects along the c-axis of the YBCO lattice. This greatly improves the structural properties of the film, ultimately resulting in almost 40% increased self-field critical current density. The underlying mechanisms behind the vacuum treatment are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These techniques have been shown to enhance the crystalline quality of each sublayer, reducing the likelihood of defect formation in subsequent deposition intervals. 55,56 Second, the underlying Ca-doped YBCO layer serves as an ideal foundation for the 4% BZO-doped YBCO layer. Notably, Ca-doped YBCO exhibits average in-plane and out-of-plane lattice parameters (a = 3.83 Å, b = 3.88 Å, and c = 11.71 Å) that closely match those of BZO-doped YBCO.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These techniques have been shown to enhance the crystalline quality of each sublayer, reducing the likelihood of defect formation in subsequent deposition intervals. 55,56 Second, the underlying Ca-doped YBCO layer serves as an ideal foundation for the 4% BZO-doped YBCO layer. Notably, Ca-doped YBCO exhibits average in-plane and out-of-plane lattice parameters (a = 3.83 Å, b = 3.88 Å, and c = 11.71 Å) that closely match those of BZO-doped YBCO.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previously, we both experimentally and theoretically determined that the crystalline quality of YBCO thin films can be enhanced through the use of multilayering (Figure a). This, in turn, extends the electron mean free path and consequently, the self-field J c (0). Utilizing a multilayer structure allows for precise control over critical factors such as uniform and nonuniform strain relaxation, as well as the formation of dislocations and other defects in layers with constrained thicknesses. This approach offers the opportunity to increase the overall thickness of the film, while maintaining improved crystalline properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it can be greatly affected by the deposition process. As an example, we have previously shown that the PLD process can be modified to produce APC-free YBCO films with significantly higher crystalline quality [31,32]. While the condition J c,v (f = 0) = 0 persists to hold for an ideal YBCO film at all temperatures, its validity even for the highest quality experimentally produced YBCO films can be questioned at high temperature range.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…However, the modified deposition mechanisms as off-axis deposition [10][11][12][13][14] and ultra-high speed interval deposition [15][16][17] as well as the post-deposition annealing treatments in oxygen atmosphere [18] have been observed to reduce the defect formation in the YBCO crystal, helping also to increase the density of the material, resulting in improved mechanical properties. It is well-known that the number of dislocations and other defects increase with increasing film thickness [19], and thus a sequential vacuum-multilayering process has recently been demonstrated to enhance the crystallinity of the entire YBCO films [20]. To improve the crystalline structure by reducing the substrate induced strain and to have a barrier between the substrate and the film, the various buffer layer combinations at the substrate-film interface or alternating layers of buffer material between the multilayered YBCO film structure have been studied.…”
Section: Introductionmentioning
confidence: 99%